2007
DOI: 10.1063/1.2644616
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ XAFS Characterization for Nitriding Process of Silica Supported Nb Catalysts Under N2-H2 Gas

Abstract: Fe-Nb/SiO 2 catalyst was prepared from NbCl 5 or peroxoniobic acid as Nb precursors. These precursor catalysts were nitrided by the TPR method under N 2 -H 2 passage (without using NH 3 ). Nb K-edge in-situ XAFS measurements were carried out during the nitriding process and revealed that the Nb species was more nitrided in the Fe-Nb/SiO 2 catalyst prepared from peroxoniobic acid than in that prepared from NbCl 5 as Nb precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Recently, we found that peroxo niobic acid (PNA) is a promising precursor for the preparation of highly dispersed Nb catalysts [13]. We have succeeded in reducing the nitriding temperature of Nb to 1173 K under a N 2 -H 2 gas stream by the addition of Fe species to a SiO 2 -supported Nb oxide precursor (Nb/SiO 2 ) [14]. In this study, we wish to report that the formation of NbN on SiO 2 support can be controlled by changing the distance between Nb and Fe species.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we found that peroxo niobic acid (PNA) is a promising precursor for the preparation of highly dispersed Nb catalysts [13]. We have succeeded in reducing the nitriding temperature of Nb to 1173 K under a N 2 -H 2 gas stream by the addition of Fe species to a SiO 2 -supported Nb oxide precursor (Nb/SiO 2 ) [14]. In this study, we wish to report that the formation of NbN on SiO 2 support can be controlled by changing the distance between Nb and Fe species.…”
Section: Introductionmentioning
confidence: 98%